2021
DOI: 10.1002/nano.202100109
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonics induced variations in molecular structure and tensile properties of silk fibers in a chemical free environment

Abstract: Ultrasonics can be used as an alternative energy supply for a green silk wet processing and for enhancement of some chemical/physical properties of biopolymers. In this work, ultrasonically treated silk fabric were compared with that of untreated and were investigated for the changes in fiber conformation structure and subsequent tensile property. Experiments were conducted under different time duration in a chemical free environment. Fiber surface energy distribution and transformation of silk secondary struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…This trend was seen again for the peak at 28.78° (IS80-0), which decreased gradually and moved left to 26.10° (IS80-180). These examples together indicate that longer ultrasonic treatment times will cause the random coil structure in SPI/SF composite nanofibers to transform into a β -sheets conformation [12] , [30] , [31] , [32] , [33] . The resulting changes of peak position, peak strength, peak shape and the secondary structure contents all indicate that an extension of ultrasonic time enhance the hydrogen bond interactions between soy and silk fibroin proteins as well as causing an increase in the β -sheet crystal content.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This trend was seen again for the peak at 28.78° (IS80-0), which decreased gradually and moved left to 26.10° (IS80-180). These examples together indicate that longer ultrasonic treatment times will cause the random coil structure in SPI/SF composite nanofibers to transform into a β -sheets conformation [12] , [30] , [31] , [32] , [33] . The resulting changes of peak position, peak strength, peak shape and the secondary structure contents all indicate that an extension of ultrasonic time enhance the hydrogen bond interactions between soy and silk fibroin proteins as well as causing an increase in the β -sheet crystal content.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon was also noted by Wang et al . [12] in a study on the ultrasonic treatment of silk fibroin from 0 to 60 min. This indicated that the longer ultrasonic times enhance the hydrogen bond interactions between protein molecular chains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, FTIR was used to identify silk proteins and evaluate their relative content by revealing the effects of melanin on their secondary structures. The peaks at 1630, 1665, and 1700 cm −1 were attributed to random coil, β-sheet, and β-turn [ 41 , 42 , 43 , 44 ]. The FTIR spectra shown in Figure 4 a showed that all the spectra corresponding to control and melanin silks have the same peaks.…”
Section: Resultsmentioning
confidence: 99%